A case of microscopic polyangiitis presenting with acute spinal subdural hemorrhage - Won Yong Suh; Eun Kyoung Lee (The Korean Society of Nephrology, 2018)
This report describes a case of a 62-year-old woman with microscopic polyangiitis (MPA) who developed acute spinal subdural hemorrhage. MPA was confirmed by positive autoantibodies to myeloperoxidase and focal segmental necrotizing and pauci-immune crescentic glomerulonephritis on renal biopsy. She did not recover from paraplegia due to acute spinal subdural hemorrhage, despite decompression operation and aggressive immunosuppression. Although spontaneous spinal hemorrhage in MPA patients is very rare, the prognosis for such patients is poor. Considering the possibility of ongoing vasculitis activity in extra-renal organs, clinicians should be very cautious to attenuate the strength of immunosuppressant drugs, even in patients with chronic or irreversible renal pathology.